(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article systematically analyzes the historical development stages of educational and cultural institutions in the Koson district of the Kashkadarya region during the years of independence. The problems of spiritual and educational crisis and outdated material and technical base inherited from the Soviet period, and the measures taken to eliminate them in the early years of independence are highlighted on the basis of archival documents and statistical indicators. Also, the modernization processes of general secondary schools, preschool education organizations, and cultural centers in the district in recent years are described in the form of textual analysis over the years